THE PUBLIC OFFICER - THE ACTIVE SUBJECT OF A CRIME - NICOLETA-ELENA BUZATU (Challenges of the Knowledge Society)
The present study intends to analyze the active subject of the crime committed by an individual - the public officer, for example - during his daily duty program or with reference to the attributions he has versus the public office he holds, in the light of the regulations provided not only by the Penal Code in force but also by the future New Penal Code, as, among the important amendments it provides, the definition of the public officer is also mentioned. In the case of such a trespassing, the active subject shall hold the quality of a public officer the way this quality is regulated by the Penal Code, even if the definition is much ampler as compared to the one given by the Statute of the Public Officers. According to Art 147, paragraph 1 Penal Code, a public officer is any individual who permanently or temporarily exercises - irrespective of his/her rank or of the way this office was appointed, a paid or unpaid task of no matter what nature or importance - in the service of a department Art 145 refers to. The regulation proposed in perfect agreement with the solutions offered by other international legislations and conventions in the domain, the definition of a public officer refers to the individual who - permanently or temporarily appointed, paid or unpaid - shall exercise attributions specific to the legislative, executive or judiciary powers, a function of public dignity or a function of any other type - alone or in a group - within a self-governing management of another economic agent or of a legal person with a whole or a greater capital, or belonging to a legally declared person capital or to a legal person considered to be of public utility - attributions connected with the object of the latter’s activity.